Creating a living breakwater : a viability study of building a kelp reef as a nature based coastal wave defence in Skutulsfjörður, Iceland - Dickson, Jonathan Michael, 1989- (2018)
Verkefnið er lokað til 01.06.2019. As ocean levels rise and storm intensities increase, coastlines are increasingly under threat from waves and seawater inundation. Hard coastal defences such as rock armour that have historically been used are still prevalent, although as coastal processes are now better understood, where possible coastal planners are shifting to nature based defences. Creating an artificial reef designed to grow kelp for wave attenuation purposes has never been attempted; consequently, the sea floor north of Ísafjörður was surveyed to assess existing flora and substrate composition to determine what would need to be done to achieve this. Literature was also reviewed to determine what would be required to promote denser, contiguous kelp growth for wave defence; kelp of sufficient density at requisite depths can attenuate wave energy by up to 85%, depending on wave distance travelled through kelp forests. A test area at Skutulsfjörður was assessed to determine kelp species, densities and substrate composition. Analysis showed that substrate composition was the major limiting factor in density and distribution, with existing kelp, mostly Laminaria hyperborea, growing mainly in four to six meter water depths. Existing kelp densities were found insufficient to attenuate wave energy and it was demonstrated that building an artificial reef with boulder sized substrate would allow kelp to grow at sufficient densities to attenuate wave energy by at least 50%. Therefore, placing low relief quarried substrate at four to 10 meter depths, designed to nurture and maintain a dense kelp forest, would reduce wave impact on Ísafjörður’s north coast. This biological defence would decrease maintenance of the shipping channel and coastal defences by reducing coastal erosion and sediment transport, therefore allowing beach accretion. Þegar yfirborð sjávar hækkar og vindstyrkur eykst þá eykst hættan á öldum og flóði við strandlengjuna. Sjóvarnargarðar hafa lengi verið notaðir og eru enn algengir. Þar sem meiri ...